2009
DOI: 10.1017/s0022215109004332
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of computed tomography for detection of extranodal spread from metastatic head and neck squamous cell carcinoma

Abstract: The sensitivity and specificity of radiological detection of extranodal spread from head and neck squamous cell carcinoma is not well reported in the literature. Accuracy of reporting improves in the hands of experienced head and neck radiologists. This finding has clinical implications for surgical planning and adjuvant therapy requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Given the lack of a defined set of criteria among studies and the varying clinical experience and training of readers in the identification of rECE, caution should be taken in comparing studies for specificity or sensitivity and generalizing these results to the general community. In 1 series with 149 patients, 2 radiologists at the same institution reading the same images were found to have rECE to pECE sensitivities of 66% and 80%, respectively, demonstrating that even within a single institution there can be varying interpretations . In our study, a single radiologist (P.S.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Given the lack of a defined set of criteria among studies and the varying clinical experience and training of readers in the identification of rECE, caution should be taken in comparing studies for specificity or sensitivity and generalizing these results to the general community. In 1 series with 149 patients, 2 radiologists at the same institution reading the same images were found to have rECE to pECE sensitivities of 66% and 80%, respectively, demonstrating that even within a single institution there can be varying interpretations . In our study, a single radiologist (P.S.…”
Section: Discussionmentioning
confidence: 52%
“…Because most of the patients in our study did not undergo surgery, our pathologic cases were small in number, and we could not reliably address the accuracy with which rECE predicted pECE. Multiple single‐institution studies have demonstrated ranges from 65% to 90% for sensitivity and 73% to 91% for specificity of rECE on CT in predicting pECE, although they are difficult to compare as results are subject to physician experience and scan quality . In our subset analysis, sensitivity and specificity were slightly lower, likely because of random error introduced by the small number of patients who underwent surgery ( n = 25).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the past 20 years, we can identify only 1 study in the English literature that has been performed to specifically assess the accuracy of CT in diagnosing ECS. In 2009, Souter et al 14 evaluated 149 neck dissections with CT image thickness between 3 and 5 mm. Iodinated contrast medium was not consistently used for all imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 12,13 from the early 1990s are contradictory, revealing sensitivities for the detection of ECS from 60% to almost 100%. More recent studies 14,15 have demonstrated sensitivities between 65%…”
mentioning
confidence: 99%